Gairaigo Derived from English in Japanese Advertising: Benefits, Drawbacks, and Global Implications - Fitri Ifi Gama (JAPANEDU: Jurnal Pendidikan dan Pengajaran Bahasa Jepang, 2023)
Gairaigo, or loanwords borrowed from foreign languages, have become a ubiquitous feature of the Japanese language, with English being the most significant influence. The use of English loanwords in Japanese advertising has become increasingly common, with many commercials and other promotional materials incorporating gairaigo in their messaging. This study aims to explore the prevalence and significance of gairaigo derived from English in Japanese advertising, examining its benefits and drawbacks, and its global implications. This study utilized qualitative approach. The method used was descriptive method. Data collection technique through literature study. Data obtained online through various academic database, a total of 19 books and 26 scientific articles, and be analysed using descriptive analyse technique. This study found important benefits of gairaigo in Japanese advertising, that are: increase product appeal to younger generations, more effective communication with international audiences, and enhanced global image of Japanese brands. However, there are also drawbacks, that are: limited accessibility for non-English speakers, potential language erosion and loss of cultural identity, and negative impact on traditional Japanese businesses. Furthermore, the global implications of gairaigo in Japanese advertising are also significant, with the influence of Japanese advertising on global marketing trends and cultural exchange and cross-linguistic communication. Overall, while the use of gairaigo in Japanese advertising can bring numerous benefits, it is important to carefully consider its potential drawbacks and cultural implications for both domestic and global audiences. By understanding the impact of gairaigo on Japanese advertising, we can gain a deeper understanding of the complex interplay between language, culture, and marketing in a global context. Further research is needed to continue exploring the impact and implications of gairaigo in Japanese advertising. Further research is needed to continue exploring the impact and implications of gairaigo in Japanese advertising.